Molecular convergence of neutralizing antibodies in human revealed by repeated rabies vaccination - Fujisawa, Mizuki; Onodera, Taishi; Kuroda, Daisuke; Kewcharoenwong, Chidchamai; Sasaki, Michihito; Itakura, Yukari; Yumoto, Kohei; Nithichanon, Arnone; Ito, Naoto; Takeoka, Shinji; Suzuki, Tadaki; Sawa, Hirofumi; et al. (npj vaccines, 2025)
Rabies vaccines require repeated immunization to robustly elicit neutralizing antibodies that prevent fatal diseases. Here, we analyzed rabies glycoprotein antibody repertoires at both polyclonal and monoclonal levels following repeated vaccination. Booster vaccination dramatically elevated the neutralizing activity of recalled antibodies, primarily targeting an immunodominant site III epitope with hydrophilic and rugged structures. Strikingly, the majority of site III-directed antibodies in the recall response used a convergent V H gene (IGHV3-30), and they exhibited more hydrophilic and shorter paratopes than non-site III antibodies, providing physicochemical advantages for binding to site III. Additionally, several amino acids on heavy chain CDR3 were identified as key sites for acquiring an ultrapotent neutralizing activity through site III binding. Our in-depth analysis of antibody repertoires revealed the molecular signatures of neutralizing antibodies generated by repeated rabies vaccination, possibly as a result of adaptive convergence.